Time Dependent Live-bed Scour Around Circular Piers under Flood Waves - Gumgum, Firat; Guney, Mehmet Sukru (Periodica Polytechnica Civil Engineering, 2020)
The aim of this study is to investigate live-bed scour under unsteady flow. During the experiments, 16 different triangular hydrographs were generated. Circular piers with three different diameters were tested under these hydrographs. Uniform bed material of63 mm diameter was used during the experiments. The effects of the peak flow rate, the duration of hydrographs and the pier diameter on scour were interpreted. It was observed that the dominant element of the scour was the flow rate during the rising limb and the sediment transport rate during the falling limb. Maximum scour depths took place near the peak flow and lower final scour depths occurred at the end of the hydrograph. Two empirical equations were derived to predict time dependent scour depth and maximum scour depth. Statistically significant determination coefficient values and scatter indices were obtained.